Accesibilidad urbana: La via ferrea que fragmenta al municipio de Palmira. (2024)
The revitalization of urban spaces through the integration of existing infrastructure, such as railways, is an exciting opportunity to transform urban fragmentation into vibrant cohesion. This architectural, urban and landscape project is proposed as an innovative solution to connect and revitalize communities separated by the presence of a railway line.